Arbuscular mycorrhizal fungi alleviate Mn phytotoxicity by altering Mn subcellular distribution and chemical forms in Lespedeza davidii - Pan, Gao; Hu, Jiayao; Zi, Zhen; Wang, Wenying; Li, Xinhang; Xu, Xiaoli; Liu, Wensheng (Frontiers in Plant Science, 2024)
Arbuscular mycorrhizal fungi (AMF) can relieve manganese (Mn) phytotoxicity and promote plant growth under Mn stress, while the roles remains unclear. To reveal the detoxification mechanisms of AMF to plants under stress, Lespedeza davidii inoculated with or without AMF (Glomus mosseae) under different Mn concentrations (0, 1, 5, 10, 20 mmol/L) was cultivated by a pot experiment, and plant biomass, physiological and biochemical characteristics, manganese absorption, subcellular distribution and chemical forms of Mn were examined. The results showed that root biomass, stem biomass, leaf biomass and total individual biomass decreased under high Mn concentrations (above 10 mmol/L), and the inoculated plants had higher biomass than the non-inoculated ones. With the rising Mn concentration, the contents of soluble sugar, soluble protein, free proline, superoxide dismutases (SOD), peroxidases (POD) and catalase (CAT) increased firstly and then decreased, while the malondialdehyde (MDA) content increased. The contents of soluble sugar, soluble protein, free proline, SOD, POD and CAT in the inoculation group were higher than those of the uninoculation group at the Mn concentration of 20 mmol/L. The content of MDA in inoculated plants were lower than that of non-inoculated ones. The inoculation of AMF enriched most of manganese in the root system when compared with the non-mycorrhizal treatment ones. Subcellular distribution of Mn indicated that most of the Mn ions were stored in the cell wall and the vacuoles (the soluble fractions), and the proportion of Mn content in the cell wall components and the vacuole components in leaves in the inoculated group was higher than non-inoculated ones. Furthermore, the proportions of Mn extracted by ethanol and deionized water in the uninoculated group in stems and roots were higher than that of the inoculated group, which suggested that AMF could convert Mn into inactive forms. In conclusion, the present study demonstrated that AMF could improve the resistance of L. davidii to Mn toxicity by increasing the activity of antioxidant enzymes, and altering the subcellular distribution and chemical forms of Mn.